2016
DOI: 10.1038/srep24630
|View full text |Cite
|
Sign up to set email alerts
|

Sports Activity after Low-contact-stress Total Knee Arthroplasty – A long term follow-up study

Abstract: The purpose of this study was to provide comprehensive long-term data about sports activity levels in patients following total knee arthroplasty (TKA) and to determine the impact of pre-operative function, pain and specific performed sports on the results. 236 patients who have undergone TKA for severe osteoarthritis of the knee were asked to provide specific information regarding exercised types of sports before surgery and after at least 10 years following TKA. Pre- and postoperative function and pain were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 33 publications
3
26
2
5
Order By: Relevance
“…Lim and colleagues also found no statistically significant difference in the change of function scores over time for both UKA and TKA [33]. Consistent with that, the other authors confirmed an association between better preoperative scores and better postoperative scores [34,35]. By examining patient-reported outcome measures from the National Joint Registry of England and Wales (NJR), no difference was found in the improvement of either knee-specific or general health outcomes between UKA and TKA in a large cohort [36].…”
Section: Discussionmentioning
confidence: 58%
“…Lim and colleagues also found no statistically significant difference in the change of function scores over time for both UKA and TKA [33]. Consistent with that, the other authors confirmed an association between better preoperative scores and better postoperative scores [34,35]. By examining patient-reported outcome measures from the National Joint Registry of England and Wales (NJR), no difference was found in the improvement of either knee-specific or general health outcomes between UKA and TKA in a large cohort [36].…”
Section: Discussionmentioning
confidence: 58%
“…No effective treatments are currently available to prevent or reverse OA progression 12 , but total knee arthroplasty (TKA) is a common surgical intervention for treating end-stage knee OA. TKA aims to relieve pain, restore loco-motor functions, correct deformities and improve quality of life 13 . Patients with knee OA undergoing TKA often present with residual functional deficits, and one important area of concern is balance impairments, which increase the risk of falls in these patients 14 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Ähnlich wie in der Hüftendoprothetik zeigt die Literatur sowohl nach UKA und TKA eine deutliche Verschiebung von High-impact-Sportarten zu Low-impact-Sportarten, wobei dieser Trend nach TKA stärker ausgeprägt ist [13]. Eine aktuelle Arbeit von Vielgut et al hat die Sportpartizipation von 236 Patienten im Langzeitverlauf nach einem mittleren Follow-up von 14,9 Jahren nach TKA beschrieben [57]. Immerhin 71 % der Patienten waren 15 Jahre post-OP noch sportlich aktiv, jedoch war auch hier eine deutliche Verschiebung hin zum low impact zu verzeichnen: von den Patienten, die prä-OP Highimpact-Sport betrieben hatten, waren es post-OP nur noch 16 %, von denen mit Intermediate-impact-Sport noch 44 %, von denen mit Low-impact-Sport noch 71 %.…”
Section: Knieendoprothetik: Allgemeine Sportfähigkeitunclassified